From the mountains to the bay the war in Virginia, January-May 1862 - Rafuse, Ethan Sepp, 1968- (Modern war studies., 2023)
"From January to July of 1862, the armies and navies of the Union and Confederacy conducted an incredibly complex and remarkably diverse range of operations in the Commonwealth of Virginia. Under the direction of leaders like Thomas 'Stonewall' Jackson, George McClellan, Joseph E. Johnston, John Rodgers, Robert E. Lee, Franklin Buchanan, Irvin McDowell, and Louis M. Goldsborough, men of the Union and Confederate armed forces marched over mountains and through sweeping valleys, maneuvered on and along great tidal rivers, bridged and waded their tributaries, battled malarial swamps, dug trenches and constructed fortifications, and advanced and retreated in search of operational and tactical advantage. In the course of these operations, the North demonstrated it had learned quite a bit from its setbacks of 1861 and was able to achieve significant operational and tactical success on both land and sea. This enabled Union arms to bring a considerable portion of Virginia under Federal control--in some cases temporarily and in others permanently. Indeed, at points during the spring and early summer of 1862, it appeared the North just might succeed in bringing about the defeat of the rebellion before the year was out. The factors that placed the Union war effort in a position in late May 1862 where this seemed by no means an unrealistic hope--even though, as subsequent events would demonstrate, the military balance in Virginia was beginning to tilt more favorably for the Confederacy--are the subject of this study, the first in a two-volume account of the war in Virginia during the first seven and a half months of 1862"--